PENGARUH RETURN DAN RISK TERHADAP KINERJA PORTOFOLIO PERUSAHAAN PADA SEKTOR INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nadia Fitriani; Desti Nur Hafifah; Sashi Ratu Agustin; Haniyah Husnul Hotimah; Aulia Zahra Putri Ardina (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to explore the impact of return and risk on the portfolio performance of companies in the industrial sector listed on the Indonesia Stock Exchange during the 2021–2025 period. Portfolio performance is an important guideline used by investors to evaluate investment success, considering the level of return and risk. The research method used is a quantitative approach with descriptive and verification characteristics. The sample in the study consisted of 10 companies operating in the industrial sector, selected through purposive sampling techniques based on certain criteria. Data were obtained from financial reports, stock prices, and other relevant information sources. The data analysis process was carried out using multiple linear regression, after undergoing classical assumption tests that included normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results of the study indicate that the return variable has no significant impact on portfolio performance. On the other hand, the risk variable has a significant negative effect on portfolio performance, indicating that increasing risk tends to decrease portfolio performance. Furthermore, the results of simultaneous testing indicate that return and risk together also have no significant effect on portfolio performance. These findings indicate that external factors beyond return and risk also influence corporate portfolio performance. This research is expected to serve as a reference for investors in better managing their investment portfolios and as a source for further research related to investment and portfolio management.